Mathematical model of vacuum membrane distillation process in bioethanol production - Ладієва, Леся Ростиславівна; Береза, О. М. (Science-based technologies, 2021)
In this work, the process of vacuum membrane distillation in the process of extracting ethanol from molasses solution was investigated. The growth of biofuel production (especially anhydrous ethanol) stimulated the search for new methods that allow to extract and concentrate it in a more efficient and profitable way; membrane technology is one of them. Membrane distillation, intended for the extraction of alcohols, is a technique using porous membranes to separate the liquid mixture, in which the driving force of the process is the partial pressure gradient on the membrane. During the process, the volatile components must change phase to pass through the membrane. The main advantage of this method is the possibility of continuous removal of ethanol at the stage of production of fuel alcohol. Membrane distillation with vacuum, designed to reduce alcohols is almost not studied. The urgent task is to create a mathematical model of the process. In this paper, a mathematical model of the dynamics of temperature and concentration at the outlet of the membrane module is developed. The formulated assumptions are accepted at development of mathematical model of process. The mathematical model takes into account the change in the concentration of ethanol in the solution at the outlet and in the vapor diffusing through the membrane. Possible control effects are considered to be the change of vacuum in the permeate channel and the flow of cooling water for condensation of ethanol vapors. . Static and dynamic characteristics of the control and perturbation channels are determined on the basis of the created mathematical model of the process. The influence of assumptions on the type and nature of dynamic properties is investigated. The system was studied in the state space. The finite difference method is used to solve the mathematical model using the Matlab software tool. The graphic results of the research are given.